Short-Term Findings From Testing EPIO, a Digital Self-Management Program for People Living With Chronic Pain: Randomized Controlled Trial - Katrine Bostrøm; Elin Børøsund; Hilde Eide; Cecilie Varsi; Ólöf Birna Kristjansdottir; Karlein M G Schreurs; Lori B Waxenberg; Karen E Weiss; Eleshia J Morrison; Hanne Stavenes Støle; Milada Cvancarova Småstuen; Audun Stubhaug; et al. (JMIR Publications, 2023)
BackgroundChronic pain conditions involve numerous physical and psychological challenges, and while psychosocial self-management interventions can be of benefit for people living with chronic pain, such in-person treatment is not always accessible. Digital self-management approaches could improve this disparity, potentially bolstering outreach and providing easy, relatively low-cost access to pain self-management interventions. ObjectiveThis randomized controlled trial aimed to evaluate the short-term efficacy of EPIO (ie, inspired by the Greek goddess for the soothing of pain, Epione), a digital self-management intervention, for people living with chronic pain. MethodsPatients (N=266) were randomly assigned to either the EPIO intervention (n=132) or a care-as-usual control group (n=134). Outcome measures included pain interference (Brief Pain Inventory; primary outcome measure), anxiety and depression (Hospital Anxiety and Depression Scale), self-regulatory fatigue (Self-Regulatory Fatigue 18 scale), health-related quality of life (SF-36 Short Form Health Survey), pain catastrophizing (Pain Catastrophizing Scale), and pain acceptance (Chronic Pain Acceptance Questionnaire). Linear regression models used change scores as the dependent variables. ResultsThe participants were primarily female (210/259, 81.1%), with a median age of 49 (range 22-78) years and a variety of pain conditions. Analyses (n=229) after 3 months revealed no statistically significant changes for the primary outcome of pain interference (P=.84), but significant reductions in the secondary outcomes of depression (mean difference −0.90; P=.03) and self-regulatory fatigue (mean difference −2.76; P=.008) in favor of the intervention group. No other statistically significant changes were observed at 3 months (all P>.05). Participants described EPIO as useful (ie, totally agree or agree; 95/109, 87.2%) and easy to use (101/109, 92.7%), with easily understandable exercises (106/109, 97.2%). ConclusionsEvidence-informed, user-centered digital pain self-management interventions such as EPIO may have the potential to effectively support self-management and improve psychological functioning in the form of reduced symptoms of depression and improved capacity to regulate thoughts, feelings, and behavior for people living with chronic pain. Trial RegistrationClinicalTrials.gov NCT03705104; https://clinicaltrials.gov/ct2/show/NCT03705104